WEB SERVER DEVELOPMENT SYSTEM WITH PHP, MYSQL, AND JSP CONFIGURATION - Yohanes, Rio; Antonius, Suyanto Edward (PROXIES, 2017)
Web server is a service to accept request from client and gives response to the client. This project builds a web server using Java Programming Language and Java Socket Programming. Java Socket Programming is used to make a connection between client and server. The web server will accept and reply the requests. This web server can execute PHP scripts and JSP scripts, including PHP scripts which access MySQL databases.